Solid-state electrochromic devices using pTMC/PEO blends as polymer electrolytes - Barbosa, P. C. (2010)
Flexible, transparent and self-supporting electrolyte films based on poly(trimethylene carbonate)/poly(ethylene oxide) ((p(TMC)/PEO) interpenetrating networks doped with LiClO4 were prepared by the solvent casting technique. These novel solid polymer electrolyte (SPE) systems were characterized by measurements of conductivity, cyclic voltammetry, differential scanning calorimetry and thermogravimetry. The incorporation of solid electrolytes as components of electrochromic devices can offer certain operational advantages in real-world applications. In this study, all-solid-state electrochromic cells were characterized, using Prussian Blue (PB) and poly-(3,4-ethylenedioxythiophene)-poly(styrenesulfonate) (PEDOT) as complementary electrochromic compounds on indium tin oxide (ITO) and poly(ethyleneterphthalate) (PET) as flexible electrodes. Assembled devices with PET/ITO/PB/SPE/PEDOT/ITO/PET “sandwich” structure were assembled and successfully cycled between light and dark blue, corresponding to the additive optical transitions for PB and PEDOT electrochromic layers. The cells required long cycle times (> 600 s) to reach full color switch and have modest stability towards prolonged cycling tests. The use of short duration cycling permitted the observation of changes in the coloration/bleaching performance in cells with different electrolyte compositions.